Electrosensory-based Search Strategies In Weakly Electric Fish - Rochman, Rebecca (Université d'Ottawa / University of Ottawa, 2015)
Effective exploration of the environment is a critical aspect of adaptive behaviour, enabling animals to identify food sources, potential mates, refuge locations, and other important resources. The particular strategies used during exploratory behaviours depend on a variety of factors including context, personality traits and natural ecology. Weakly electric fish rely specifically on a short-range electric sense to search and locate objects in their environment in low-light conditions. However, little is known about the exploratory strategies used. We characterized the exploratory movements of two species of weakly electric fish, Apteronotus leptorhynchus and Apteronotus albifrons, in a laboratory setting. Our results suggest that there are behavioural differences between species in their exploratory strategies. Apteronotus albifrons spent more time in the open, travelled at a slower speed when out in the open, and had a higher total feeding time. Interestingly, Apteronotus leptorhynchus had a higher total displacement and preference for wall-following. A subsequent study on the behavioural function of wall-following in the two species suggested that wall-following is used for exploration in weakly electric fish, rather than for protection, and is not an artifact of restricted movement and tank shape.
Keywords: Weakly electric fish; Exploration; Wall-following